2017
DOI: 10.1002/ange.201612599
|View full text |Cite
|
Sign up to set email alerts
|

Regiocontrolled Direct C−H Arylation of Indoles at the C4 and C5 Positions

Abstract: An effective and practical strategy has been established for the direct and site‐selective arylation of indoles at the C4 and C5 positions with the aid of a readily accessible, cheap, and removable pivaloyl directing group at the C3 position. This transformation shows good functional‐group tolerance and could serve as a powerful synthetic tool for the synthesis of medicinally relevant compounds. This method and those developed in previous research together enable the regiocontrolled direct arylation of indole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…However, this method suffers from low functional group tolerance and a limited substrate scope [ 14 22 ]. The few described methods for C5 and C6 indole functionalization provide limited functional group tolerance [ 19 , 23 ]. Recently, Baran et al developed a remarkable example of iridium-catalyzed ligand-controlled selective C6 tryptophan borylation;however, even this groundbreaking directing group-free method requires protecting groups and is unable to tolerate tryptophan containing cyclic dipeptides [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this method suffers from low functional group tolerance and a limited substrate scope [ 14 22 ]. The few described methods for C5 and C6 indole functionalization provide limited functional group tolerance [ 19 , 23 ]. Recently, Baran et al developed a remarkable example of iridium-catalyzed ligand-controlled selective C6 tryptophan borylation;however, even this groundbreaking directing group-free method requires protecting groups and is unable to tolerate tryptophan containing cyclic dipeptides [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“… 9 The Pd-catalyzed C4 arylation was studied by Zhi, and the acetyl-directing group has been removed in a separate step. 10 Recently, Miura et al reported the use of thiomethyl ether as an efficient directing group for C4 C–H functionalization. 11 In another study, You described a pivaloyl group-assisted C2/C4 heteroarylation of indoles by a controlled metalation tuning.…”
mentioning
confidence: 99%
“…We further examined the scope of using C3pivaloyl indoles as coupling partners with BBr 3 ; these compounds reacted with a high regioselectivity to produce C4-hydroxylated indoles (Fig. 3b) 59 . We first evaluated the influence of the N-H protection groups on the indoles.…”
Section: Resultsmentioning
confidence: 99%